Viscosity Solutions of Uniformly Elliptic Equations without Boundary and Growth Conditions at Infinity. (19th September 2011) - Galise, G.; Vitolo, A.
Abstract : We deal with fully nonlinear second-order equations assuming a superlinear growth in u with the aim to generalize previous existence and uniqueness results of viscosity solutions in the whole space without conditions at infinity. We also consider the solvability of the Dirichlet problem in bounded and unbounded domains and show a blow-up result.